DEVICE FAILURES AND COMPLIANCE GAPS IN INFUSION PUMPS: RETROSPECTIVE TRENDS FROM FDA AND MEDSUN REPORTS - ANGELIN STAFFIN; T. SUDHEER KUMAR; R. KAMARAJ (The Bioscan, 2025)
This study conducted a retrospective data analysis and structured literature review to examine the safety, malfunction trends, and regulatory actions concerning infusion pumps from 2022 to 2024, utilizing data from the FDA Product Classification database, MEDSUN, and FDA Recalls. A total of 580 adverse event causes were reported, with the FRN (general-purpose infusion pump) model accounting for nearly 79% of these events, and potential patient harm cited in 46.6% of all incidents. Analysis of device issues revealed pump malfunctions as the most frequent problem (approximately 145 cases), followed by inaccurate infusion rates (around 65 cases) and alarm malfunctions (approximately 60 cases); the FRN device consistently contributed the most to all malfunction types, including 91.7% of alarm malfunctions and 85.7% of battery issues. Infusion pump recalls significantly increased, from 28 in 2022 to 55 in 2024, with the FRN model implicated in most recalls, including 15 Class I recalls in both 2023 and 2024. Observed regulatory compliance gaps, such as inadequate design validation, ineffective Corrective and Preventive Actions (CAPA) for recurring issues, and insufficient human factors engineering, underscore the critical need for targeted CAPA measures and enhanced regulatory oversight, particularly for the FRN model, to improve the overall safety and reliability of infusion pump technologies.